2018
DOI: 10.3389/fpls.2018.01829
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Resistance to Fusarium Head Blight in Synthetic Hexaploid Wheat Derived From Aegilops tauschii and Diverse Triticum turgidum Subspecies

Abstract: Synthetic hexaploid wheat (SHW) can serve as a bridge for the transfer of useful genes from Aegilops tauschii and tetraploid wheat (Triticum turgidum) into common wheat (T. aestivum). The objective of this study was to evaluate 149 SHW lines and their 74 tetraploid parents for their genetic diversity, breeding values and inter-genomic interactions for resistance to Fusarium head blight (FHB). The genetic diversity analysis was performed based on the population structure established using 4,674 and 3,330 polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
2
19
1
Order By: Relevance
“…Except a few variations, the performances of selected lines were consistent and the results were reproducible. The variation in FHB resistance in the M4 lines or in the parental lines observed during this study can be attributed to variability in FHB reactions, unfavorable environmental conditions for disease development or escape from inoculation which commonly occur in field FHB evaluation as documented by other researchers 43 45 . Stability and inheritance of resistance of M4 lines were further tested by crossing two M4 lines (E.25.11 and 41,708.72) with a susceptible parental line, Ben and developing BC 1 :F 3 families and testing them by Fusarium inoculation, which confirmed that the modification is stable, genetic and heritable.…”
Section: Discussionsupporting
confidence: 51%
“…Except a few variations, the performances of selected lines were consistent and the results were reproducible. The variation in FHB resistance in the M4 lines or in the parental lines observed during this study can be attributed to variability in FHB reactions, unfavorable environmental conditions for disease development or escape from inoculation which commonly occur in field FHB evaluation as documented by other researchers 43 45 . Stability and inheritance of resistance of M4 lines were further tested by crossing two M4 lines (E.25.11 and 41,708.72) with a susceptible parental line, Ben and developing BC 1 :F 3 families and testing them by Fusarium inoculation, which confirmed that the modification is stable, genetic and heritable.…”
Section: Discussionsupporting
confidence: 51%
“…A possible explanation could be that current durum wheat, mostly descending from germplasm of the warm and summer‐dry Mediterranean basin, has not been exposed to relevant disease pressure and selection for improved FHB resistance had historically low priority (Buerstmayr et al, ). It is also hypothesized that the D genome of hexaploid wheat may play a major role in reducing disease severity as synthetic wheat lines, generated by crossing tetraploid T. turgidum with Aegilops tauschii , were more resistant than the T. turgidum parents (Szabo‐Hever et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…durum with A. tauschii accessions, followed by chemical chromosome doubling. These so‐called re‐synthesised bread wheats or synthetic hexaploid wheats (SHWs) are made with the goal of introducing new functional trait diversity into modern germplasm (Kishii, 2019), notably disease resistance genes (Mujeeb‐Kazi et al ., 1996; Das et al ., 2016; Szabo‐Hever et al ., 2018; Kishii et al ., 2019; Mohler et al ., 2020) but also, for example, a higher yield (Hao et al ., 2019). The International Maize and Wheat Improvement Center (CIMMYT), Texcoco, Mexico has been developing many synthetic hexaploid wheats since the 1960s (Gordon et al ., 2019), but several other programmes exist, for example at NIAB, Cambridge, UK.…”
Section: Introductionmentioning
confidence: 99%